2022
DOI: 10.1590/1980-220x-reeusp-2021-0423
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with umbilical cord clamping in term newborns

Abstract: OBJECTIVE: To identify factors associated with umbilical cord clamping in term newborns and to compare the recording of clamping time in the medical record with what was observed. METHOD: Cross-sectional study, with 300 mothers-infants, in a university hospital. Clamping time and medical records were observed, and a structured questionnaire was applied to postpartum women for sociodemographic variables. Bivariate analysis, multivariate Poisson Regression model, and Kappa concordance test were performed. RESU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 22 publications
1
3
0
1
Order By: Relevance
“…In this study, the percentage of delayed cord clamps (DCC) was found to be 53.09% (95% CI: 48.09-58.03%). This finding is comparable to the findings of studies conducted in Nepal (48%) (20) and Brazil (53.7%) (29). It is also in accordance with a study conducted in five public hospitals in Bangladesh, Nepal, and Tanzania, which shows that 47.3-73% of the newborns received DCC (32).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In this study, the percentage of delayed cord clamps (DCC) was found to be 53.09% (95% CI: 48.09-58.03%). This finding is comparable to the findings of studies conducted in Nepal (48%) (20) and Brazil (53.7%) (29). It is also in accordance with a study conducted in five public hospitals in Bangladesh, Nepal, and Tanzania, which shows that 47.3-73% of the newborns received DCC (32).…”
Section: Discussionsupporting
confidence: 89%
“…For this study, a checklist that was adopted from studies done in different literature was used (12,16,(25)(26)(27)(28)(29)(17)(18)(19)(20)(21)(22)(23)(24). Data were collected through participant observation to prevent bias.…”
Section: Data Collection Procedures (Instrument Personnel)mentioning
confidence: 99%
See 1 more Smart Citation
“…Noting that higher rates of exclusive or predominant breastfeeding after hospital discharge and assistance in maintaining body temperature and better neurological outcomes are observed in full-term newborns from birth to 4 years of age. Despite the benefits shown, high rates of early/immediate clamping are still identified, which is considered an outdated care protocol (STRADA, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Importante ressaltar que a ligadura precoce do cordão umbilical é indicada para neonatos que necessitam de reanimação. Assim, constata-se que esse amplo conhecimento disponível não se traduz em ações no cotidiano de alguns profissionais (23) .…”
Section: Discussionunclassified